The value of coordinated analysis of multimodal atherosclerotic plaque imaging in the assessment of cardiovascular and cerebrovascular events - Yu, Shun; Zheng, Yonghong; Dai, Xiaomin; Chen, Huangjing; Yang, Shengsheng; Ma, Mingping; Huang, Feng; Zhu, Pengli (Frontiers in Cardiovascular Medicine, 2024)
Background: Atherosclerosis (AS) can involve multiple vascular beds, but previous studies have focused on the analysis of single-site AS plaques.Objective: The aim of this study was to explore the differences or similarities in the characteristics of internal carotid artery, cerebral artery, and coronary artery atherosclerotic plaque between patients with ASCVD and those without events. This is a provisional file, not the final typeset article stenosis grades (p=0.030) and shown significant differences in LPV, LPR, and CPV (p=0.044, 0.030, 0.020). In coronary plaques, the ASCVD group had plaques with greater stenosis (p< 0.001), more severe stenosis grades (p <0.001), larger volumes (p=0.001), longer length (p=0.008), large FLPV (p=0.012), large FPV (p=0.002), higher FPR (p=0.043) compared with the non-event group. There were significant differences in stenosis (HR-VWI, CCTA: p<0.001, p<0.001), stenosis grades (HR-VWI, CCTA: p<0.001, p<0.001), plaque length (HR-VWI, CCTA: p=0.028, p<0.001) and plaque volume (HR-VWI, CCTA: p=0.013, p=0.018) between non-event plaque, non-culprit plaque and culprit plaque. In image analysis of HR-VWI, there were differences between IPHR (p<0.001), LPR (p=0.001), FPV (p=0.011) and CPV (p=0.015) among the three groups of plaques. FLPV and FPV were significantly different among the three different plaque types from coronary artery (p=0.043, p=0.022).Conclusion: For the same patient, there is a consistent pattern of change in plaque characteristics between cervicocephalic and coronary arteries.